The Architecture of Dezzak Grand Mosque, Iranian Baluchestan With Reference To Prophet Mohammad Mosque in Medina - Hossein Sarhaddi-dadian; Sabereh Malekzadeh; Zuliskandar Ramli (Journal of Islamic Architecture, 2022)
This paper investigates the architecture of the Dezzak Grand Mosque in Saravan City for the first time to the best of our knowledge. One of the most important research problems was the lack of sufficient information about the Dezzak Mosque. Considering that some of the Islamic geographers had sporadically mentioned an old mosque in the southeast of Iran, comprehensive field research was not done in this regard. This study compares Dezzak Mosque the oldest mosque in South East of Iran with the Prophet Mohmmad Mosque in Medina and other mosques of Early Islam in Iran such as Fahraj Tarikhane Damghan mosques in Iran from the perspective of style and architectural features. With the arrival of the Muslim Arabs to Iran and acceptance of the new religion, Islam, Iranian Muslims were engaged in the construction of mosques in this country. The Dezzak Mosque was one of them. The mosque has a square plan with a corridor, which is surrounded by circular columns and arches around the courtyard with clay raw. The columns have a diameter of 1.5 meters around the courtyard, which is most on the South Side. Raw bricks for the construction of the building and palm trees are used to cover the roof. Recent studies show that the Dezzak Mosque in terms of stylistic influences of the Khorasani style is the first Islamic-Iranian style. Dezzak Mosque is similar to the Prophet Mosque in Medina in case of plan, materials, and architectural features, and also it has been influenced by Tarikhane Damghan and Fahraj as the oldest mosques In Iranian Plateau.